2022-RA-588-ESGO Nemvaleukin alfa monotherapy and in combination with pembrolizumab in patients with advanced solid tumours: ARTISTRY-1. (20th October 2022) - Vaishampayan, Ulka; Tomczak, Piotr; Muzaffar, Jameel; Winer, Ira; Rosen, Seth D; Hoimes, Christopher J; Chauhan, Aman; Spreafico, Anna; Lewis, Karl D; Bruno, Debora S; Dumas, Olivier; McDermott, David F; et al.
Abstract : Introduction/Background: Nemvaleukin alfa (nemvaleukin, ALKS 4230) is an engineered cytokine that selectively binds to the intermediate-affinity interleukin-2 (IL-2) receptor to preferentially activate anti-tumour CD8 + T and natural killer cells with minimal expansion of immunosuppressive regulatory T cells. Nemvaleukin was designed to leverage anti-tumour effects of the IL-2 pathway while mitigating toxicities associated with activation of the high-affinity IL-2 receptor. Methodology: ARTISTRY-1 (NCT02799095 ) is a 3-part, first-in-human, phase 1/2 study of intravenous nemvaleukin +/- pembrolizumab in patients with advanced solid tumours. Parts A (monotherapy dose escalation to 10 µg/kg/day ×5/cycle), B (monotherapy in patients with melanoma or renal cell carcinoma [RCC]), and C (combination with nemvaleukin 3 or 6 µg/kg/day ×5/cycle and pembrolizumab every 21 days) were included. Investigator-assessed anti-tumour activity (RECIST v1.1) and safety are reported as of 29 October 2021. Results: In Part A (N=46), nemvaleukin recommended phase 2 dose was 6 µg/kg/day intravenously ×5/cycle. The maximum tolerated dose was not reached. Nemvaleukin monotherapy demonstrated durable anti-tumour activity in RCC (objective response rate [ORR], 18.2% [4/22]) and melanoma (ORR, 8.7% [4/46]), with 2 partial responses (PRs; 1 unconfirmed) in 30 patients with cutaneous melanoma (ORR, 6.7%) and 2 PRs (1 unconfirmed) in 6 patients with mucosal melanoma (ORR, 33.3%). Durable anti-tumour activity was also observed for combination therapy (ORR, 16.1% [22/137]; disease control rate [DCR], 59.9%), including in platinum-resistant ovarian cancer, with 2 complete responses and 2 PRs (1 unconfirmed) in 14 patients (ORR, 28.6% [4/14]; DCR, 71.4%). 43 patients remain on therapy. Most common grade 3/4 treatment-related adverse events in Parts B and C, respectively, were anaemia (9%, 10%), neutropaenia (34%, 9%), and decreased neutrophil count (12%, 9%). Conclusion: Nemvaleukin was generally well tolerated. Durable responses were observed with monotherapy and combination therapy in heavily pre-treated patients across a range of tumours, warranting further investigation.